Pu guṃ Mruiʹ hoṅʻʺ Mranʻʺ ka pā Gū prokʻ krīʺ Bhu rāʺ - Kyoʻ Ṅrimʻʺ, Ūʺ, 1928- (Ūʺ Canʻʺ Vaṅʻʺ, 1992)
Study on the Mon inscriptions on the walls of Mraṅʻʺ ka pā Gū prokʻ krīʺ Bhu rāʺ, cave temple in Pagan, Burma; includes text with Burmese translation, and history of the temple.